2020
DOI: 10.1097/tp.0000000000003406
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Renal Transplant Recipients With SARS-CoV-2 Infection in the Eye of the Storm: A Comparative Study With Waitlisted Patients

Abstract: Background. Patients with chronic kidney disease stage 5 and those on immunosuppression are particularly vulnerable and are shielded as per public health strategy. We present our experience of coronavirus disease 2019 (COVID-19) transplant patients in one of the most affected parts of the UK with direct comparison to waitlisted patients. Methods. A single-center prospective study of symptomatic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) positive waitlisted and transplant patients was undertak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 21 publications
1
33
0
1
Order By: Relevance
“…Such studies are of interest as they would help make better informed decisions regarding whether to proceed with transplantation during the pandemic versus having the patient accrue time on the waiting list. We summarized the studies comparing transplant patients to wait-listed patients with COVID-19 disease in Table 3 9,11,[30][31][32][33][34][35] .…”
Section: Comparing Waitlisted Patients To Transplant Recipients With Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies are of interest as they would help make better informed decisions regarding whether to proceed with transplantation during the pandemic versus having the patient accrue time on the waiting list. We summarized the studies comparing transplant patients to wait-listed patients with COVID-19 disease in Table 3 9,11,[30][31][32][33][34][35] .…”
Section: Comparing Waitlisted Patients To Transplant Recipients With Covid-19mentioning
confidence: 99%
“…Another explanation is the increased exposure of waitlisted patients to virus while receiving in-center hemodialysis. Most studies, which were done in Europe, identified a much higher COVID-19 related mortality in transplant recipients versus waitlisted patients, ranging 20-37% vs 5-16%, respectively 9,11,[31][32][33][34][35] . The largest series came from France for the period March 1st through June 1, 2020 that identified 275 deaths among the 42,812 kidney transplant recipients and 144 deaths among the 16,210 candidates 35 .…”
Section: Comparing Waitlisted Patients To Transplant Recipients With Covid-19mentioning
confidence: 99%
“…In particular, the T cell response is significantly suppressed in this population [ 1 ••, 2 •, 3 , 4 ]. At the outset of the pandemic, when the natural history of COVID-19 infection could only be conjectured, there was bona fide concern that immunosuppressed patients would be at increased risk for infection with SARS-CoV-2 and would experience unacceptably high mortality rates [ 3 7 ]. Faced with this hypothesis, solid organ transplant programs needed to make important decisions about very practical matters [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Around the world, transplant centers made individualized decisions about the conduct of their programs, though several themes were mostly consistent: pre-operative testing of recipients and donors for COVID-19 infection, minimizing immunosuppression, rigorous limited recipient selection, and the use of telemedicine in the outpatient setting when possible [ 1 ••, 3 , 5 , 8 , 9 ••]. In this paper, we explore the variations on these management strategies, to demonstrate that the transplant center response to the COVID-19 pandemic developed to address the individual needs of the centers, but ultimately reflected the desire to protect patients from any modifiable excessive harm.…”
Section: Introductionmentioning
confidence: 99%
“…Since we know neither the actual SARS-CoV-2 viral load in these COVID-19 patients nor the differences in viral load across tissues and cell types, we think that when used at the recommended clinical doses, an antiviral effect of CsA or tacrolimus could not be ruled out. Interestingly, and unexpectedly, a recent study in the UK showed that SARS-CoV-2 infections were less frequent in transplanted patients receiving immunosuppressive therapy (mainly tacrolimus, cyclosporine and steroids) compared with those on a transplant waiting list, with no immunosuppression [7]. Similarly, an international, multicentric study showed that only 144 out of 9845 patients with kidney transplants and immunosuppressive therapy were hospitalized with COVID-19, and most of them, with comorbidities [8], suggest possible protection by tacrolimus or CsA, acting upon undetermined mechanisms.…”
mentioning
confidence: 99%